Artichoke (Cynara scolymus L.) water extract alleviates palmitate-induced insulin resistance in HepG2 hepatocytes via the activation of IRS1/PI3K/AKT/FoxO1 and GSK-3β signaling pathway - Aihua Deng; Yun Wang; Kerui Huang; Peng Xie; Ping Mo; Fengying Liu; Jun Chen; Kaiyi Chen; Yun Wang; Bing Xiao (BMC, 2023)
Abstract Background Artichoke (Cynara scolymus L.) is a typical element of a traditional Mediterranean diet and has potential health advantages for insulin resistance (IR) and type 2 diabetes mellitus (T2DM). This study aims to evaluate the effect and underlying mechanism of artichoke water extract (AWE) on palmitate (PA)-induced IR in human hepatocellular carcinoma (HepG2) cells. Methods The effect of AWE on cell viability was determined using CCK8 assay. Cellular glucose uptake, glucose consumption, glucose production, and glycogen content were assessed after AWE treatment. The gene expression and protein levels were examined by real-time polymerase chain reaction (qRT-PCR) and western blotting. Results The results showed that AWE dose-dependently increased cell viability in IR HepG2 cells (P < 0.01). AWE treatment significantly promoted glucose uptake and consumption, decreased glucose production, and increased the cellular glycogen content in IR HepG2 cells (P < 0.01). Mechanistically, AWE elevated the phosphorylation and total protein levels of major insulin signaling molecules in IR HepG2 cells, which resulted in a decrease in the expression of phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphatase (G6Pase) and the inhibition of glycogen synthase (GS) phosphorylation in IR HepG2 cells. Furthermore, the protective effect of AWE on IR HepG2 cells might be ascribed to the inhibition of the endoplasmic reticulum (ER) stress. Conclusion We conclude that AWE may improve glucose metabolism by regulating IRS1/PI3K/AKT/FoxO1 and GSK-3β signaling associated with the inhibition of ER stress in IR HepG2 cells induced by PA.